Analysis of Challenges and Strategies of the Women Leadership and Economic Empowerment - Patrini. Dhanalakshmi, Dr. K. Lakshmi Sirisha, CHITTURI. LAKSHMI,Dr. Siva sankar Mandal Baidya, Dr. P. Jayalakshmi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
After independence, the Indian Government, from time to time has taken several Constitutional, statutory measures to promote women. The government programme for Women development began as early as 1954 in India but the actual participation began only in 1974. The National policy for the Empowerment of women was adopted in 2001. The goal of this policy is to bring about the advancement, development and empowerment of women. At present, the Government of India has introduced number of schemes for women operated by different departments and ministries. Women are almost half of the population having enormous potential but being underutilized for the development of the nation. The active participation of women need to strengthen and streamline the role of women in the development of various other sectors like entrepreneurship and leadership by harnessing their power towards nation building and to attain accelerated economic growth. World Economic profile of women show that, women represents 50% of the world population make up 30% of the official labour force, perform 60% of all working hours, receive 10% of world income and own even less than one per cent of the world’s property (World Economic survey report). The main aim of the study is to analyse the challenges and Strategies of the women Leadership and economic empowerment. The study is based on secondary data from Reports, Magazines, Journals and web resources. This paper reviews studies done in women leadership in the context of theory of Leadership.